IMPLEMENTATION OF THE SANCTION OF WHIP FOR THE COMMUNITY ACEH IN THE ERSFECTIVE OF ISLAMIC LAW - Mhd. Fauzan Simanjuntak; R. Soesilo; Habibullah Harahap (PT. Radja Intercontinental Publishing, 2023)
Customary Law is the entire code of community behavior that applies and has sanctions and has not been codified. Islamic law is one of the laws used by the Aceh government in enforcing Sharia law. The aim of this research is to what extent is the enforcement of caning laws carried out by the Aceh government regulations on convicts in cases of violations of Islamic law, why are there differences in caning sentences in a decision, and is there a connection to customs in sharia law in Aceh. Based on the research results, the caning law imposed in Qanun No. 6 of 2014 concerning the Jinayat Law did not receive any rejection from the people of Aceh. enforcement of Qanun no. 6 of 2014 was carried out by the Wilayatul Hisbah police, which is part of the civil service police. The determination of the defendant's sentence is carried out by the Panel of Judges at trial. Implementation of the whip law Qanun no. 6 of 2014 is expected to have a deterrent effect on perpetrators and serve as an example so that the people of Aceh do not violate Qanun no. 6 of 2014. There is an application of the law of caning which is applied to violators of Qanun No. 6 of 2014, different sentences are given according to the type of offense committed by the defendant